Role of lipoprotein lipase variants in metabolic disorders and cardiovascular diseases - Rafaqat, Sana; Rafaqat, Saira; Sharif, Saima; Klisić, Aleksandra (Archives of Pharmacy, 2024)
Lipoprotein lipase (LPL) is a glycoprotein that is produced and secreted into the interstitial space in various tissues, including the cardiac muscle, adipose tissue, macrophages, and skeletal muscle. LPL activity could be affected by genetic alterations which result in changes in lipid metabolism. This review article only focuses on reporting the recent studies which mainly explain the role of the LPL gene variants in metabolic syndrome and cardiovascular diseases. There are over 100 LPL gene variants, but this review article reported rs1801177, rs118204069, rs118204057, rs118204060, rs118204068, rs268, and rs328 as the most common in metabolic syndrome patients. In cardiovascular diseases, LPL variants rs1801177, rs268 and rs328 were the most prevalent. Therefore, it is suggested that further studies should be conducted to identify the LPL gene variants in other cardiovascular diseases, including cardiac arrhythmia. This review article concludes that LPL deficiency and dysfunction are associated with many diseases, such as obesity, insulin resistance, diabetes, chylomicronemia, atherosclerosis, myocardial infarction, coronary artery disease, and stroke.